Use of Human Umbilical Cord and Its Byproducts in Tissue Regeneration - Velarde, Francesca; Castañeda, Verónica; Morales, Emilia; Ortega, Mayra; Ocaña, Edwin; Álvarez-Barreto, Jose; Grunauer, Michelle; Eguiguren, Luis; Caicedo, Andrés (Frontiers in Bioengineering and Biotechnology, 2020)
The fresh or cryopreserved human umbilical cord (HUC) and its by-products, such as cells and extracts, have different uses in tissue regeneration. Defining what HUC byproduct is more effective in a particular application is a challenge. Furthermore, the methods of isolation, culture and preservation, may affect cell viability and regenerative properties. In this article, we review the HUC and its byproducts applications in research and clinical practice. We present our results of successful use of HUC as a patch to treat gastroschisis and its potential to be applied in other conditions. Our in-vitro results show proliferation and migration by using an acellular HUC extract. Our goal is to promote standardization of procedures and point out that applications of HUC and its byproducts, as well as the resulting advances in regenerative medicine, will depend on rigorous quality control and on more research in this area.